Current Information of Medicinal Plants : Pseuderanthemum Palatiferum (Nees) Radlk - Padee, Peerawit; Nualkaew, Somsak (Journal of Health Science of Thailand, 2018)
Pseuderanthemum palatiferum (Nees) Radlk. is the medicinal plant belonging to Acanthaceae family. It is a shrub, multi branches with simple opposite decussate leaves and easily cultivate. It was first found in the northern region of Vietnam in 1990. According to folklore medicine of Vietnam and Thailand the leaves of this plant were recommended for treatment of hypertension, diarrhea, arthritis, hemorrhoids, stomach ache, tumor, colitis, bleeding, wound, constipation, flu, colon cancer, nephritis, and diabetes. The objectives of this article was to review the information about chemical and pharmacological studies of P. palatiferum and provide pertinent information for consumers on appropriate use. From literatures review it was found that this plant was composed of many chemical constituents such as β-sitosterol, stigmasterol, kaempferol, apigenin, phytol, triterpenoids saponin, and salicylic acid including essential amino acids such as lysine, methionine and threonine. Pharmacological activities of this plant on anti-oxidant, anti-bacterial, anti-fungal and anti-diarrhea activities were reported. There are some pharmacological activities corresponding to its chemical constituents and traditional use such as anti-diarrhea related to E. coli and antioxidant activities. However, there are some traditional uses still not confirmed by pharmacological test in cases of hypertension, arthritis, hemorrhoids, stomachache, tumor, colitis, bleeding, wound, constipation, flu, colon cancer, nephritis, or diabetes. The treatment of these diseases with P. palatiferum should proceed with great caution and only with more information on its effectiveness and toxicity.